The relation between macroeconomic ambient and healthcare qualified workers: the case of the Republic of Serbia - Ćurčić, Mihailo; Matić, Iva; Milojević, Irena (Anali Ekonomskog fakulteta u Subotici, 2021)
Taking into account that the available capacities of human and material resources are key for a stable and sustainable health system of a country, this paper deals with the relation between the macroeconomic environment and the movement of the number of employees in the health system in the case of the Republic of Serbia. The aim of this paper is to make recommendations for further research based on the conducted analyses and to review the existing trends critically, in order to raise the level of public awareness in efforts to reduce the outflow of professional staff. The available official data of the institutions of the health system of the Republic of Serbia were used in the research, and time series from 2010 to 2018 were included.